Dopamine D2 Receptor-Mediated Heterologous Sensitization of AC5 Requires Signalosome Assembly. (12th March 2012) - Ejendal, Karin F. K.; Dessauer, Carmen W.; Hébert, Terence E.; Watts, Val J.
Abstract : Chronic dopamine receptor activation is implicated in several central nervous system disorders. Although acute activation of G α i -coupled D2 dopamine receptors inhibits adenylyl cyclase, persistent activation enhances adenylyl cyclase activity, a phenomenon called heterologous sensitization. Previous work revealed a requirement for G α s in D2 -induced heterologous sensitization of AC5. To elucidate the mechanism of G α s dependency, we expressed G α s mutants in G α s -deficient G n a s E 2 − / E 2 − cells. Neither G α s -palmitoylation nor G α s -Gβγ interactions were required for sensitization of AC5. Moreover, we found that coexpressing βARKct-CD8 or Sar1(H79G) blocked heterologous sensitization. These studies are consistent with a role for G α s -AC5 interactions in sensitization however, Gβγ appears to have an indirect role in heterologous sensitization of AC5, possibly by promoting proper signalosome assembly.